Single Nanocrystals Studies of Upconverting Nanoparticles. (24th April 2020) - Krajnik, Bartosz; Holodnik, Katarzyna; Noculak, Agnieszka; Golacki, Lukasz; Kostiv, Uliana; Horak, Daniel; Podhorodecki, Artur
Abstract : Single-molecule imaging and spectroscopy are well-established experimental techniques that operate at the limits of the analytical chemistry and spatial resolution of conventional optical microscopy. It allows for observation of individual, often unique properties of molecules and nanoparticles, not accessible with other techniques. Due to the sparse distribution of nanoparticles, mutual interactions are limited, which improves the reliability of the experimental techniques operating at the level of single nanoparticles. This approach also makes it possible to conduct research without disrupting the results with effects related to the distribution of the physicochemical properties of investigated objects. It enables also to separate phenomena related to mutual interactions between the investigated objects. For these and other reasons, this technique is increasingly used for nanocrystals investigations. However, very little has been still done using these techniques in the area of upconverting nanoparticles. In this work, we demonstrate the results of single nanocrystals studies of upconverting nanocrystals (UCNCs) doped with Yb 3+ and Er 3+ ions. In particular, we present the impact of the heterogeneity of the nanocrystals on the optical properties of UCNCs. That, in turn, limits the use of the UCNCs in the practical application f. e. in nanothermometry.